Quantitative analysis of the mandible for sex estimation (Research, Society and Development, 2021)
This study aimed to investigate the applicability of mandibular measures for sex estimation in human dry skulls from two Brazilian bone collections. This was a blind diagnostic study with 471 mandibles of 215 females and 256 males. The variables considered were: bigonial-width; bicondylar-width; right/left condylar process width; coronoid width; distance between the mandibular foramina; distance between the mental foramina; distance between the genial spinal foramina and the right/left mandibular foramina; right/left coronoid process height; right and left mandibular ramus height; right/left mandibular thickness; anterior mandibular thickness; maximum width of the right and left mandibular ramus; minimum width of the right and left mandibular ramus; mandibular-length; and the mandibular angle. Discriminant analysis was performed to check for associations concerning sex both for individual and total measurements. The statistical analysis indicated that all variables were found to be significantly associated with sex. When applied to males and females, the stepwise method correctly classified 77.50% and 80.20% of the cases, respectively, with a total percentage of agreement of 78.70%. The left mandibular ramus height (74.80%) and the bigonial width (77.60%) were the variables with the highest agreement rates among males and females, respectively. Equations were generated from the discriminant analysis for each variable and a unique formula for the six variables showed the highest preference for sex. All mandibular measures were statistically different between the sexes, suggesting that the mandible plays an important role in forensic anthropology as a source of quantitative information for sex estimation.